2016
DOI: 10.18632/oncotarget.8069
|View full text |Cite
|
Sign up to set email alerts
|

High expression of C-C chemokine receptor 2 associates with poor overall survival in gastric cancer patients after surgical resection

Abstract: BackgroundBeing a critical chemokine receptor in chemoattracting myeloid cells into tumor tissues, C-C chemokine receptor 2 (CCR2) has been detected in many malignant tumors. This study aims to evaluate the prognostic value of CCR2 expression in patients with gastric cancer after surgery.ResultsCCR2 expression was detected in the accessory cells around gastric cancer cells in a diffused manner. CCR2 high expression was correlated with tumor invasion depth (P=0.006 and P=0.004, respectively), lymph node metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Thus, CCR2‐positive cells infiltrations were shown not in the stomach but rather in the small intestine. Previous study and our study have also reported that CCR2‐positive cells were seldom seen in gastric tissues but were present in gastric cancer tissues . Since central injection of Ucn 2 affects on gastrointestinal tract through activating the sympathetic nervous system, inhibition of the vagus nerve may worsen intestinal mucosal inflammation.…”
Section: Discussionsupporting
confidence: 61%
“…Thus, CCR2‐positive cells infiltrations were shown not in the stomach but rather in the small intestine. Previous study and our study have also reported that CCR2‐positive cells were seldom seen in gastric tissues but were present in gastric cancer tissues . Since central injection of Ucn 2 affects on gastrointestinal tract through activating the sympathetic nervous system, inhibition of the vagus nerve may worsen intestinal mucosal inflammation.…”
Section: Discussionsupporting
confidence: 61%
“…The efficacy of CCL2‐CCR2 axis inhibition has been widely investigated in numerous preclinical experiments. CCL2 and CCR2 can function as diagnostic biomarkers, 164 and are correlated with the prognosis and poor overall survival in cancer patients 105,165 . Given the critical roles of the CCL2‐CCR2 signalling axis in tumorigenesis, a series of clinical trials targeting this axis have been launched continually (Table 2).…”
Section: Ccl2‐ccr2‐associated Targeted Therapymentioning
confidence: 99%
“…CCL2 has been suggested as a potential biomarker for several types of cancer, including prostate [ 105 , 106 , 107 , 108 ]. Given the critical roles of the CCL2-CCR2 signaling axis in tumorigenesis, a series of clinical trials targeting this axis have been carried out in several cancers [ 102 , 107 ].…”
Section: Targeting Macrophages In Cancer Therapy and Its Application In Pcmentioning
confidence: 99%